IDENTIFICATION OF SECONDARY METABOLIC AND TEST OF ACTIVITY ETHYL ACETATE FRACTION OF BANGUN¬- BANGUN (Coleus amboinicus Lour.) LEAVES AS ANTIOXIDANT - Kasta Gurning (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2020)
Antioxidants have an important role in delaying the oxidation process and preventing the occurrence of degenerative diseases in the body. Antioxidants consist of synthetic and natural; the use of synthetic antioxidants in a relatively long period is hazardous so that the use of natural antioxidants is considered more potential and safe for the body. The process of extracting secondary metabolites from the leaves of bangun-bangun (Coleus amboinicus L.) is carried out by the maceration method with methanol, then partitioned in stages with n-hexane, chloroform, and ethyl acetate. This research intends to identify secondary metabolites and test antioxidant activity from the ethyl acetate fraction with the DPPH method. Phytochemical screening results of ethyl acetate fraction showed the different secondary metabolite groups such as alkaloids, phenolics & polyphenols, flavonoids, coumarin, and triterpenoids. Antioxidant activity (IC50) obtained is 64.97 with a healthy category, so that the potential to be used as a natural antioxidant.